2008
DOI: 10.1038/onc.2008.323
|View full text |Cite
|
Sign up to set email alerts
|

Oncogene activation in melanocytes links reactive oxygen to multinucleated phenotype and senescence

Abstract: Contrary to malignant melanoma, nevi are a benign form of melanocytic hyperproliferation. They are frequently observed as precursor lesions of melanoma, but they also feature biochemical markers of senescence. In particular, evidence for oncogene-induced melanocyte senescence as natural means to prevent tumorigenesis has been obtained in nevi with mutated B-Raf V600E. Here, we demonstrate that strong oncogenic growth factor receptor signalling drives melanocytes into senescence, whereas weaker signals keep the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 79 publications
(67 citation statements)
references
References 65 publications
(63 reference statements)
1
62
1
Order By: Relevance
“…High levels of Xmrk generate a substantial ROS load (Leikam et al, 2008). It is known that EGF receptors, a group of RTKs that includes Xmrk, can mediate ROS induction by activating NADPH oxidases (Browe and Baumgarten, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…High levels of Xmrk generate a substantial ROS load (Leikam et al, 2008). It is known that EGF receptors, a group of RTKs that includes Xmrk, can mediate ROS induction by activating NADPH oxidases (Browe and Baumgarten, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown that HERmrk can induce the generation of reactive oxygen species (ROS) (Leikam et al, 2008;Leikam et al, 2013) and that Xmrk-transgenic fish melanomas display a ROS-responsive protein signature (Lokaj et al, 2009). As ROS are potent activators of NF-kB, we investigated their role in NF-kB induction in Hm cells.…”
Section: Nf-kb Is Activated By Xmrkmentioning
confidence: 99%
See 2 more Smart Citations
“…A recent study revealed that a multinucleated phenotype is brought about by oncogenic signaling-dependent ROS production in melanocytes. 55 We have to determine whether ROS formation is due to activation of signaling cascade(s) besides ROS formation by the nanoparticles themselves.…”
Section: Discussionmentioning
confidence: 99%